PKM Increasing the Economic Value of Tuna Fish ‘Trips’ Waste in Pedungan Village, Denpasar - Darmadi, Ni Made; Arjana, I Gusti Made; Edi, Dewa Gede Semara; Lestari, Ni Made Dwi; Antara, I Kadek Riko Adi (Asian Journal of Community Services, 2024)
By Providing Added Value from waste is a very important thing to implement in developing the Blue Economy. In this PkM Activity, waste handling is carried out in stages and sustainably, until the Zero Waste principle is achieved. The Community Service activity carried out at the IRT owned by Ni Wayan Sarimi (Partnersa) turned Tuna Fish Skin waste into a food product in the form of fish skin crackers. The meat part is used as Fish Abon. The method of Community Service is using the interview method and participation in the practice of making tuna fish floss. The purpose of this PkM is to provide solutions to Partners to make meat from waste Tuna fish skin into Tuna fish floss. . This PkM activity has been published in Print and Electronic Media. Activity videos are uploaded on YouTube.